Training as an Activity for Optimizing Emotional and Personality Wellbeing - Karapetyan, L; Zotova, O (KnE Life Sciences, 2018)
Emotional and personality wellbeing (EPW) represents a complex system capturing a great number of elements, subjects, and objects that differ in a qualitative diversity of internal bonds and complexity of system–structural relationships with other systems and social milieu. This training aimed at optimizing emotional and personality wellbeing including a psychological impact on various components of the respondents’ implicit perceptions about their wellbeing, the individual’s awareness of wellbeing factors, their own limitations, adaptive resources, ability to reconstruct notional sphere and a constructive fashion of behavior. Extreme conditions of the activity predetermine most destructive effects on emotional and personal wellbeing. In light of this, the authors introduce the training program in the group of rescuers whose job involves a great number of physical and psychological risks. The training incorporates 5 four-hour thematic blocks and implies the use of such techniques as reflexive self-analysis and focusing, active visualization, techniques aimed at semantic processes’ facilitating, positive reinterpretation, as well as elements of bodily therapy, action-based and gaming techniques, coaching, sand therapy. The effectiveness of the training offered was confirmed upon applying the Wilcockson criterion that showed the validity of differences in SEPW (Self-evaluation of Emotional and Personality Wellbeing) indicators before and after the training: positive indicators have become significantly higher, negative – significantly lower; difference between mean values of integrated EPW indicators and mean value of EPW index have grown significantly. Thus, the training effectiveness was confirmed due to increased awareness of EPW self-evaluation and a wider repertoire of techniques providing normalization of actual psycho-emotional state. The authors underline that the developed training scenario can be used in any vocational group with the account of specific character of its members’ activities. Keywords: emotional and personality wellbeing, self-evaluation, optimization, training